SENSITIVITY OF RIMERIA TENELLA TO SOME ANTICOCCIDIAL DRUGS - Ghani, A.; A. Al-Attar, M. (The Iraqi Journal of Veterinary Medicine, 1988)
The effeciancy of some anticoccidial drugs were tested for the treatment fo E. tenella infection in chickens. Four drugs were used. The first was composed of Sulphaquinoxalin and Trimethoprim; the Second of Sulpaquinoxalin Diaveridine; the third of Sulphaquinoxalin and Amprolium, and the fourth of Amprolium and Furaltadon. Criteria used in the evaluation of drugs performance were, weight gain; feed consumption and conversion; total oocyst counts, and packed cell volume. The highest percent of protection (102%) was obtained with the first drug. The second, third and fourth drugs gave 99.8, 64.4, and 45.7 percents of protection, respectively.